The effect of anodising on the fatigue performance of self-tapping aluminium screws. (June 2015) - Gröber, D.; Georgi, W.; Sieber, M.; Scharf, I.; Hellmig, R.J.; Leidich, E.; Lampke, T.; Mayr, P.
Highlights: Hard anodising does not affect the static tensile strength. Hard anodising reduces fatigue strength of screws EN AW-6056 and 6082. Hard anodising does not affect or even increase fatigue strength of screws EN AW-7068 depending on the load horizon. Hard anodising reduces the scatter of endured fatigue cycles. Abstract: Self-tapping aluminium screws are an innovative joining technology for the assembly of lightweight components in industrial scale. It has been established in the past that porous anodic oxide coatings in many cases reduce the fatigue strength of specimens without notches. In the present work, the fatigue behaviour of notched specimens, i.e. self-tapping screws made from aluminium alloys EN AW-6056, 6082 (both in a conventional state and in a fine-grained state produced by equal channel angular pressing – ECAP) and 7068 with and without oxide coatings is examined. The coatings are produced by hard anodising and are necessary for the thread-forming process during assembly. While the coatings do not affect the static tensile strength, they reduce the fatigue strength for the specimens of the 6056 and the 6082 alloy. For the 7068 alloy a slight increase in fatigue strength is discovered on a low load horizon. The scatter of endured fatigue cycles until fracture of specimens is generally reduced by the anodic oxide coatings.